Characterisation of Toll-like receptors 4, 5 and 7 and their genetic variation in the grey partridge - Vinkler, Michal; Bainová, Hana; Bryjová, Anna; Tomášek, Oldřich; Albrecht, Tomáš; Bryja, Josef (Genetica, 2015)
Toll-like receptors (TLRs) are a cornerstone of vertebrate innate immunity. In this study, we identified orthologues of TLR4, TLR5 and TLR7 (representing both bacterial- and viral-sensing TLRs) in the grey partridge (Perdix perdix), a European Galliform game bird species. The phylogeny of all three TLR genes follows the known phylogeny of Galloanserae birds, placing grey partridge TLRs (PePeTLRs) in close proximity to their turkey and pheasant orthologues. The predicted proteins encoded by the PePeTLR genes were 843, 862-863 and 1,047 amino acids long, respectively, and clearly showed all TLR structural features. To verify functionality in these genes we mapped their tissue-expression profiles, revealing generally high PePeTLR4 and PePeTLR5 expression in the thymus and absence of PePeTLR4 and PePeTLR7 expression in the brain. Using 454 next-generation sequencing, we then assessed genetic variation within these genes for a wild grey partridge population in the Czech Republic, EU. We identified 11 nucleotide substitutions in PePeTLR4, eight in PePeTLR5 and six in PePeTLR7, resulting in four, four and three amino acid replacements, respectively. Given their locations and chemical features, most of these non-synonymous substitutions probably have a minor functional impact. As the intraspecific genetic variation of the three TLR genes was low, we assume that either negative selection or a bottleneck may have reduced TLR population variability in this species.
Keywords: molekulární evoluce; Models, Molecular; orgánová specificita; Toll-Like Receptor 4; toll-like receptor 5; genetická variace; Organ Specificity; Genetic Variation; toll-like receptor 4; Animals; Protein Conformation; Gene Expression; molekulární modely; zvířata; Toll-Like Receptor 5; fylogeneze; Galliformes; exprese genu; Toll-Like Receptor 7; toll-like receptor 7; Phylogeny; konformace proteinů; Evolution, Molecular